HLA Class II Antibodies at the Time of Kidney Transplantation and Cardiovascular Outcome: A Retrospective Cohort Study. Issue 4 (April 2020) - Malfait, Thomas; Emonds, Marie-Paule; Daniëls, Liesbeth; Nagler, Evi V.; Van Biesen, Wim; Van Laecke, Steven
Abstract : Background: The negative role of HLA class II donor-specific antibody on graft outcome is well recognized. However, the potentially negative cardiovascular effects of preformed HLA class II antibodies and donor HLA in kidney transplant recipients (KTRs) remain unestablished. Methods: We conducted a single-center, retrospective cohort study including 1115 KTRs (2003–2016) with up to 4449 person-years of follow-up after transplantation and a median follow-up time of 5.1 years (interquartile range, 2.7–7.6). We evaluated the unadjusted and multivariable-adjusted association between pretransplant HLA class I and II antibodies, as well as HLA-DR1 donor/recipient genotype and the primary (major adverse cardiac and cerebrovascular event [MACCE] or all-cause mortality) and secondary (MACCE or cardiovascular mortality) outcome. Results: In a multivariate Cox proportional hazard model, HLA class II antibodies before transplantation were associated with increased adjusted hazard ratio (aHR) for MACCE or all-cause mortality (aHR, 1.71 [1.13–2.60]; P = 0.012) even after adjustment for time-varying covariate graft loss (aHR, 1.68 [1.08–2.62]; P = 0.022) and biopsy-proven acute rejection (aHR, 1.71 [1.13–2.60]; P = 0.012). HLA class II antibodies were also associated with increased aHR for the secondary outcome, MACCE, or cardiovascular mortality (aHR, 1.92 [1.12–3.30]; P = 0.018). We investigated the effect of donor and recipient HLA-DR1 on these outcome parameters and demonstrated that KTRs with HLA-DR1 positive donors had an increased aHR for MACCE with all-cause (aHR, 1.45 [1.09–1.94]; P = 0.012) and cardiovascular mortality (aHR, 1.49 [1.00–2.22]; P = 0.05). Conclusions: Prior sensitization against HLA class II antigens is associated with unfavorable long-term cardiovascular outcome in KTRs independent of graft loss or rejection. Recipients of an HLA-DR1 donor also have an impaired cardiovascular outcome. Abstract : Supplemental Digital Content is available in the text.